EFEKTIVITAS IMPLEMENTASI PERATURAN GUBERNUR DAERAH ISTIMEWA YOGYAKARTA NOMOR 42 TAHUN 2009 TENTANG KAWASAN DILARANG MEROKOK DI STASIUN KERETA API BESAR YOGYAKARTA - Kartiko Bramantyo Dwi Putro; Aufarul Marom; Titik Djumiarti; Ari Subowo (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
Special Region of Yogyakarta is one of provinces with high prevalence of active smokers. Cigarettes is one of the addictive substances containing approximately 4,000 chemicals in which 200 are toxic and very harmful to human health, especially passive smokers. Air pollution caused by cigarette smoke affects the quality of polluted clean air. The Provincial Government shall take steps by issuing the Regulation of Governor of Special Region of Yogyakarta Number 42 Year 2009 about No Smoking Area. Yogyakarta Railway Station is one of the no smoking areas listed in this rule. This study aims to measure the extent to which the implementation of established rules and see the inhibiting and supporting factors. This research uses descriptive qualitative method. This research uses the approach of policy accuracy, the accuracy of the implementation, the accuracy of the target, the accuracy of the environment, the accuracy of the process. This research uses the Theory of Implementation George C Edwards III. The results show that this regulation has been implemented in Yogyakarta Great Station. Obstacles are found that in terms of coordination between implementing agencies are still lacking, and the absence of clear legal sanctions. The authors recommend that the Provincial Government make a Regional Regulation governing the area of smoking prohibited with clear implementation standards and contains strict legal sanctions. The authority of Yogyakarta Railway Station needs to increase supervision in the station area. Society must also be aware and always obey this rule.